Impact of outreach education program on outcomes of neonates with hypoxic ischemic encephalopathy. Issue 5 (22nd July 2020) - Mohammad, Khorshid; Dharel, Dinesh; Abou Mehrem, Ayman; Esser, Michael J; Paul, Renee; Zein, Hussein; Scott, James N; Fiedrich, Elsa; Murthy, Prashanth; Dossani, Salma; Kopores, Kaley; Kowal, Derek; et al.
Abstract: Aim: To evaluate the impact of outreach education targeting neuroprotection on outcomes of outborn infants with moderate-to-severe hypoxic ischemic encephalopathy (HIE). Methods: A retrospective cohort study of infants admitted with moderate-to-severe HIE was conducted following the implementation of outreach education in January 2016. Key interventions were early identification and referral of infants with encephalopathy utilizing telemedicine and a centralized communication system, hands-on simulation, and interactive case discussion and dissemination of clinical management guidelines and educational resources. The association between the intervention and a composite outcome of death and/or severe brain injury on brain magnetic resonance imaging (MRI) was tested controlling for the confounding factors. Results: Of 165 neonates, 37 (22.4%) died and/or had a severe brain injury. This outcome decreased from 35% (27/77) to 11% (10/88) following the implementation of outreach education (P<0.001). Eligible infants not undergoing therapeutic hypothermia within 6 hours from birth decreased from 19.5% (15/77) to 4.5% (4/88). The use of inotropes decreased from 49.3% (38/77) to 19.6% (13/88). Any core temperature below 33°C was recorded for 20/53 (38%) before and 16/78 (21%) after, while those within the target range of 33°C to 34°C at admission to a tertiary care facility increased from (15/53) 28% to (51/88) 58%. Outreach education was independently associated with decreased composite outcome of death and/or severe brain injury on MRI (adjusted odds ratio 0.2; 95% confidence interval 0.07 to 0.52). Conclusion: Outreach education targeting neuroprotection for infants with moderate-to-severe HIE was associated with a reduction in death and/or severe brain injury.